Problematics of sociology : the Georg Simmel lectures, 1995 - Smelser, Neil J. (University of California Press, 1997)
"Based on the Georg Simmel Lectures delivered at Humboldt University in the spring of 1995, Problematics of Sociology is a distillation of Neil Smelser's reflections after nearly four decades of research, teaching, and thought in the field of sociology." "Each chapter considers a different level of analysis: micro, meso, macro, and global. Within this framework, the themes considered range over a variety of topics, including the place of the rational and nonrational in social action and in social science theory; social institutions as imagined entities; the eclipse of social class; and the decline of the nation-state as a focus of solidarity."--Jacket.